Formation of the Information Competence of Pedagogical Staff in the Conditions of Personality-Based Training - as an Important Factor of Successful Career - Adashboev, Shavkiddin; Choriev, Ilkhom (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In this paper, the authors consider the problems associated with the formation of information competence of students in personality-oriented education. Consider the psychological and pedagogical possibilities of using modern information technology in the educational process. Reveal three levels of ownership of ICT competences in the process of formation of the student's personality.